2021
DOI: 10.1200/jco.21.00605
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Cytoreduction and Carboplatin Hyperthermic Intraperitoneal Chemotherapy for Platinum-Sensitive Recurrent Ovarian Cancer: An MSK Team Ovary Phase II Study

Abstract: PURPOSE The purpose of this phase II study was to evaluate hyperthermic intraperitoneal chemotherapy (HIPEC) with carboplatin for recurrent ovarian cancer during secondary cytoreductive surgery. MATERIALS AND METHODS Patients were intraoperatively randomly assigned to carboplatin HIPEC (800 mg/m2 for 90 minutes) or no HIPEC, followed by five or six cycles of postoperative IV carboplatin-based chemotherapy, respectively. Based on a binomial single-stage pick-the-winner design, an arm was considered winner if ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 40 publications
1
85
0
Order By: Relevance
“…The pharmacokinetic profile of carboplatin is similar to that of cisplatin with fewer side effects, but thermal enhancement is poor, and the depth of penetration in tumor nodules is much lower [38, 44, 45]. In a recently published phase II trial, there was no benefit of the addition carboplatin HIPEC to secondary CRS and 5 cycles of systemic chemotherapy (SC) compared to secondary CRS with 6 cycles of SC [5]. Doxorubicin is not an active drug for SC in ovarian cancer but has a highly favorable pharmacokinetic profile and low toxicity that has led to its use for performing HIPEC usually in combination with cisplatin [46-48].…”
Section: Rationale and Pitfalls Of Hipecmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetic profile of carboplatin is similar to that of cisplatin with fewer side effects, but thermal enhancement is poor, and the depth of penetration in tumor nodules is much lower [38, 44, 45]. In a recently published phase II trial, there was no benefit of the addition carboplatin HIPEC to secondary CRS and 5 cycles of systemic chemotherapy (SC) compared to secondary CRS with 6 cycles of SC [5]. Doxorubicin is not an active drug for SC in ovarian cancer but has a highly favorable pharmacokinetic profile and low toxicity that has led to its use for performing HIPEC usually in combination with cisplatin [46-48].…”
Section: Rationale and Pitfalls Of Hipecmentioning
confidence: 99%
“…In the near past, most of the evidence favoring or disfavoring the use of HIPEC came from retrospective studies comprising heterogeneous groups of patients, with a greater heterogeneity in the treatment protocols, making it difficult to derive significant conclusions [2]. To date, 3 randomized clinical trials (RCTs) have been published, 2 favoring the use of HIPEC at different time points, 1 disfavoring its use [3-5]. Along with the emergence of HIPEC as a promising surgical therapy, targeted therapies like bevacizumab and poly adenosine diphosphate-ribose polymerase (PARP) inhibitors have been developed that have shown a survival benefit in selected patients in RCTs [6-8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the methodological quality of that trial was only moderate. A recent randomized phase II trial assigned recurrent EOC patients to either CRS and HIPEC (Carboplatin 800 mg/m 2 for 90 min) or CRS alone, followed by five or six cycles of postoperative IV carboplatin-based chemotherapy, respectively [64]. Based on a 'pick-the-winner' design, an arm would be considered superior if at least 17 out of 49 patients were without progression at 24 months follow-up.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Likewise, a recent prospective randomized trial in 98 patients with relapsed ovarian cancer undergoing secondary cytoreductive surgery also did not show any impact of HIPEC on peri-operative morbidity, progression-free survival or overall survival 4. Admittedly, a number of retrospective trials have shown benefit of HIPEC in ovarian cancer.…”
mentioning
confidence: 95%
“…The hype around hyperthermic intraperitoneal chemotherapy (HIPEC) started two decades ago when a randomized trial comparing surgery and HIPEC against palliative chemotherapy only in patients with colorectal cancer showed favorable results 1. In ovarian cancer, data from three prospective randomized controlled trials and several retrospective trials are available 2–5…”
mentioning
confidence: 99%